A biomass-derived hard carbon / graphite composite negative electrode material and its preparation method and application
By composited with graphite, biomass-derived hard carbon/graphite composite negative electrode material was prepared, which solved the problem of uneven current density distribution of the negative electrode material of lithium-ion battery, and achieved the effects of high specific capacity, excellent rate performance and current density uniformity.
Patent Information
- Application Number
- CN202411958331.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The negative electrode materials of existing lithium-ion batteries have uneven current density distribution during charging, resulting in uneven lithium deposition tendency, and traditional negative electrode materials are difficult to meet the development needs of high capacity density, low cost and long cycles.
By pre-carbonizing, crushing and acid leaching the delignin-based wood-based biomass, a hard carbon precursor of wood-based biomass is obtained, and fused and carbonized with graphite, dispersant and coating agent to prepare a biomass-derived hard carbon/graphite composite negative electrode material, and its mixing ratio is adjusted to improve performance.
It has achieved high specific capacity, high efficiency, good rate performance and uniform current density distribution of biomass-derived hard carbon/graphite composite anode material, and is suitable for high energy density battery systems.
Smart Images

Figure CN119764396A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium battery electrode materials, and specifically relates to a biomass-derived hard carbon / graphite composite negative electrode material. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely used in many fields such as portable electronic devices, electric vehicles (EVs) and smart grids. At present, the negative electrode materials of lithium-ion batteries are mainly carbon materials (graphite, hard and soft carbon, etc.), transition metal oxides and silicon materials. Graphite has the advantages of abundant resources, low price, good conductivity and high reversible capacity, and is the mainstream negative electrode material for commercial lithium-ion batteries. However, during charging, the current density distribution of graphite negative electrode becomes very uneven, which causes the graphite particles near the negative electrode / diaphragm interface to be lithiated faster than other parts of the negative electrode, and has a higher tendency to lithium deposition as charging continues. And with the development trend of negative electrode materials towards high capacity density, low cost and long cycle, traditional negative electrode materials are increasingly difficult to meet the status quo. Therefore, the development of new high-performance, green and low-cost negative electrode materials for use in lithium-ion batteries has become a research hotspot.
[0003] The strategy of hard carbon-coated "isotropic" microcrystalline graphite is expected to significantly improve the rate performance of graphite from the material design level. Biomass-derived hard carbon materials are a type of hard carbon material derived from agricultural / forestry waste / by-products. They are currently the focus of attention for the preparation of hard carbon materials due to their environmental friendliness and low cost. Although the improved rate performance of hard carbon is attractive for high-power applications, its poor ICE as well as high redox potential and low density limit its application in high-energy-density battery systems. The study found that this energy / power density trade-off was overcome by preparing a composite anode from a uniform mixture of graphite / hard carbon active material particles, and rationally adjusting the electrode performance in a synergistic manner to improve current uniformity and reduce lithium plating during fast charging while maintaining a sufficiently high battery energy density.
[0004] In order to improve the capacity, fast charging performance and first effect of biomass hard carbon / graphite composite materials, patent CN 115832292A discloses a modified fast-charging graphite negative electrode material and its improved method and application. The method first pre-treats the graphite under a CO2 atmosphere, then composites the graphite with fungus residue extract, bamboo source, etc., and then undergoes hydrothermal treatment and carbonization to finally obtain modified fast-charging graphite. The raw materials used in this patent, such as biomass fungus residue and bamboo source, have defects such as high ash content and unstable sources, which make it difficult to effectively control their stability, seriously affecting their negative electrode performance. Patent CN 111244407A describes a method for preparing a hard carbon precursor, which uses asphalt as a raw material, and obtains a hard carbon / graphite composite material by bonding the hard carbon precursor to graphite and additives, and coating the surface. Although the first effect is improved, the improvement in capacity is not significant. Therefore, it is urgent to explore the appropriate mixing ratio of biomass hard carbon and graphite to prepare biomass hard carbon / graphite composite negative electrode materials with high specific capacity, high first coulombic efficiency, good rate performance and uniform current density distribution. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the above-mentioned technologies, the present invention provides a biomass-derived hard carbon / graphite composite negative electrode material.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] In a first aspect, the present invention provides a biomass-derived hard carbon / graphite composite negative electrode material, which includes hard carbon and graphite; the carbon source of the hard carbon is delignified wood-based biomass; the mass ratio of the hard carbon to the graphite is 1:(0.33-3).
[0008] In a certain embodiment, the wood-based biomass is wood, preferably one or more of poplar, pine, fir and basswood, such as poplar, pine or basswood.
[0009] In a certain embodiment, the graphite can be various conventional types of graphite in the art, preferably one or more of artificial graphite, natural flake graphite, mesophase carbon microbeads and expanded graphite; for example, artificial graphite.
[0010] In one embodiment, the particle size D of the composite negative electrode material is 50 11-18 μm; for example, 12 μm, 13 μm, 14 μm, 16 μm or 17 μm.
[0011] In one embodiment, the true density of the composite negative electrode material is 2-3 g / cm 3 , more preferably 2.2-2.3 g / cm 3 , for example 2.23 g / cm 3 , 2.24g / cm3 , or 2.25g / cm 3 .
[0012] In one embodiment, the tap density of the composite negative electrode material is 0.9-1.2 g / cm 3 , preferably 0.95-1.05g / cm 3 , for example 0.95g / cm 3 , 0.99g / cm 3 , 1.00g / cm 3 , 1.01g / cm 3 , or 1.02g / cm 3 .
[0013] In one embodiment, the specific surface area of the composite negative electrode material is 2.5-3.5 m 2 / g, for example 2.7m 2 / g, 3.1m 2 / g, 3.2m 2 / g, or 3.5m 2 / g.
[0014] In a certain embodiment, in the composite negative electrode material, the mass ratio of the hard carbon to graphite is 1:0.8-1.5.
[0015] In a certain embodiment, in the composite negative electrode material, the mass ratio of the hard carbon to graphite is 1:0.33, 1:1 or 1:3.
[0016] In a second aspect, the present invention provides a method for preparing a biomass-derived hard carbon / graphite composite negative electrode material, which comprises the following steps:
[0017] S1: pre-carbonizing the delignified wood-based biomass to obtain pre-carbonized wood-based biomass;
[0018] S2: crushing and acid-leaching the obtained pre-carbonized wood-based biomass to obtain a wood-based biomass hard carbon precursor;
[0019] S3: fusing and carbonizing the obtained wood-based biomass hard carbon precursor, graphite, dispersant and coating agent to obtain the biomass-derived hard carbon / graphite composite negative electrode material.
[0020] In step S1, the delignified wood-based biomass is prepared by a conventional delignification treatment step in the art, preferably, by the following steps:
[0021] S0: The wood-based biomass is immersed in a mixed solution of an aqueous sodium hydroxide solution and an aqueous sodium sulfite solution, and then treated with hydrogen peroxide.
[0022] In step S0, the molar ratio of the sodium hydroxide to the sodium sulfite is a conventional ratio in delignification treatment in the art. Preferably, the molar ratio of the sodium hydroxide to the sodium sulfite is (3-4):1, preferably 3.125:1.
[0023] In step S0, the concentration of the sodium hydroxide aqueous solution is a conventional concentration for delignification treatment in the art. Preferably, the concentration of the sodium hydroxide aqueous solution is 1-3 mol / L, for example, 2.5 mol / L.
[0024] In step S0, the concentration of the sodium sulfite aqueous solution is a conventional concentration in delignification treatment in the art. Preferably, the concentration of the sodium sulfite aqueous solution is 0.3-0.5 mol / L, such as 0.4 mol / L.
[0025] In step S0, the mass volume ratio of the wood-based biomass and the mixed solution is a conventional ratio of delignification treatment in the art. Preferably, the mass volume ratio of the wood-based biomass and the mixed solution is (0.1-0.5) g:1 mL, preferably (0.2-0.3) g:1 mL, for example 0.27 g:1 mL.
[0026] The volume ratio of the mixed solution to hydrogen peroxide is a conventional ratio for delignification treatment in the art. Preferably, the volume ratio of the mixed solution to hydrogen peroxide is (2-3):1, preferably 2.5:1.
[0027] In a certain embodiment, the concentration of the hydrogen peroxide is 25%-30%, preferably 30%.
[0028] In step S1, the pre-carbonization reaction is carried out in conventional equipment in the art, preferably in a muffle furnace.
[0029] In step S1, the reaction temperature of the pre-carbonization is a conventional temperature in the art. Preferably, the reaction temperature of the pre-carbonization is 350-600°C, preferably 500°C.
[0030] In step S1, the temperature rise rate of the pre-carbonization is a conventional heating rate in the art. Preferably, the temperature rise rate of the pre-carbonization is 4-6°C / min, preferably 5°C / min.
[0031] In step S1, the pre-carbonization reaction time is the conventional reaction time in the art. Preferably, the pre-carbonization time is 1-3 hours, preferably 2 hours.
[0032] In step S2, the pulverizing operation is performed in conventional equipment in the art, preferably, in a ball mill.
[0033] In step S2, the rotation speed of the ball mill is a conventional rotation speed in the art, preferably, the rotation speed of the ball mill is 400-800 rpm, preferably 500 rpm.
[0034] In step S2, the pulverizing time is the conventional pulverizing time in the art, preferably, the pulverizing time is 1-5 hours, preferably 2 hours.
[0035] In one embodiment, in step S2, the particle size D of the crushed material is 50 5-30 μm, preferably 20 μm.
[0036] In step S2, the acid used for acid leaching is a conventional acid in the art, preferably one or more of hydrochloric acid, sulfuric acid and nitric acid, such as hydrochloric acid.
[0037] In step S2, the concentration of the acid used for acid leaching is the conventional hydrochloric acid concentration in the art. Preferably, the concentration of the acid is 0.8-1.5 mol / L, preferably 1 mol / L.
[0038] In step S2, the acid leaching time is conventional in the art, preferably, the acid leaching time is 3-5 hours, preferably 4 hours.
[0039] In one embodiment, in step S2, after the acid leaching is completed, washing and drying are required.
[0040] In one embodiment, the washing is washing with deionized water and ethanol in sequence.
[0041] The drying method is a conventional drying method in the art, preferably vacuum drying.
[0042] The drying temperature is a conventional drying temperature in the art, preferably, the drying temperature is 80-100°C, preferably 100°C.
[0043] The drying time is the conventional drying time in the art, preferably, the drying time is 8-24 hours, preferably 10 hours.
[0044] In step S3, the amount of the dispersant used can be conventional in the art, preferably, based on the sum of the wood-based biomass hard carbon precursor and graphite, the mass ratio of the sum of the wood-based biomass hard carbon precursor and graphite to the dispersant is 100:(2.5-8.0), for example, 100:5.
[0045] In step S3, the amount of the coating agent can be conventional in the art, preferably, based on the sum of the wood-based biomass hard carbon precursor and graphite, the mass ratio of the sum of the wood-based biomass hard carbon precursor and graphite to the coating agent is 100:(1-25), for example, 100:5.4.
[0046] The dispersant is a conventional dispersant in the art, preferably polyoxyethylene dodecylphenol ether or polyvinyl pyrrolidone (PVP).
[0047] The coating agent is a conventional coating agent in the art, preferably an organic matter of shaped carbon, such as condensed oil. The coking value of the coating agent is 5%-90%, such as 6%.
[0048] In step S3, the carbonization reaction is carried out in conventional equipment in the art, preferably in a tubular furnace.
[0049] In step S3, the carbonization reaction is carried out under a conventional inert atmosphere in the art, preferably nitrogen.
[0050] In step S3, the carbonization temperature is conventional in the art, preferably, the carbonization temperature is 500-1000°C, preferably 900°C.
[0051] In step S3, the temperature rise rate of the carbonization is conventional in the art, preferably, the temperature rise rate of the carbonization is 2-3°C / min, preferably 2°C / min.
[0052] In step S3, the carbonization time is the conventional carbonization time in the art, preferably, the carbonization time is 4-8 hours, preferably 8 hours.
[0053] In one embodiment, in step S3, after the carbonization is completed, the temperature needs to be lowered to room temperature.
[0054] In one embodiment, the room temperature is 15-40°C.
[0055] In a third aspect, the present invention provides a biomass-derived hard carbon / graphite composite negative electrode material obtained by the preparation method described above.
[0056] In a fourth aspect, the present invention provides a use of the biomass-derived hard carbon / graphite composite negative electrode material as described above as a negative electrode material.
[0057] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0058] The reagents and raw materials used in the present invention are commercially available.
[0059] The positive and progressive effects of the present invention are:
[0060] (1) The present invention performs delignification treatment on biomass materials, which provides more channels and sites for subsequent impregnation, grafting modification and deposition without destroying the biomass cell structure. The woody biomass materials are particularly selected, and the obtained biomass-derived hard carbon / graphite composite material has the characteristics of uniform particle size distribution and high specific capacity.
[0061] (2) The present invention preferably achieves synergistic performance by adjusting the mixing ratio of biomass hard carbon / graphite, and utilizes the pore structure of biomass hard carbon and the highly disordered carbon layer composition to further increase the lithium ion deintercalation channel and shorten the lithium ion transmission path; in the process of fusion coating, the adhesion of the coating agent will well enable the biomass hard carbon to be coated on the artificial graphite, achieving a stable composite of the coating layer and the graphite carrier, thereby forming a conductive path with a network structure, improving the rate performance and capacity of the lithium battery negative electrode, and significantly improving the uniformity of the current density.
[0062] (3) The biomass-derived hard carbon / graphite composite negative electrode material prepared by the present invention has a simple preparation method, convenient operation, low equipment investment, low raw material price and abundant source, which can reduce production costs and facilitate promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 Schematic diagram of the structure of biomass-derived hard carbon / graphite composite negative electrode material DETAILED DESCRIPTION
[0064] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0065] Unless otherwise specified, the room temperature in the examples refers to 15-40°C.
[0066] The graphite and condensate oil used in the examples were purchased from Fujian Shanshan Technology Co., Ltd. 50 The particle size is 13 μm; the coking value of the condensed oil is 6%.
[0067] Example 1
[0068] (1) 20 g of natural poplar wood was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified natural poplar wood.
[0069] (2) The delignified natural poplar wood of step (1) is placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization is completed, the wood is cooled to room temperature, the product is collected, and the collected product is placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0070] (3) The pre-carbonized wood-based biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0071] (4) Artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected, placed in a tubular furnace, and carbonized under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0072] Example 2
[0073] (1) 20 g of natural poplar wood was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified natural poplar wood.
[0074] (2) The delignified natural poplar wood of step (1) is placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization is completed, the wood is cooled to room temperature, the product is collected, and the collected product is placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0075] (3) The pre-carbonized wood-based biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0076] (4) Artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 75:25:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected, placed in a tubular furnace, and carbonized under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0077] Example 3
[0078] (1) 20 g of natural poplar wood was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified natural poplar wood.
[0079] (2) The delignified natural poplar wood of step (1) is placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization is completed, the wood is cooled to room temperature, the product is collected, and the collected product is placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0080] (3) The pre-carbonized wood-based biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0081] (4) Adding artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP in a mass ratio of 25:75:5.4:5 into a fusion device for fusion treatment at the same time to obtain a mixture of biomass hard carbon and graphite; collecting the above-mentioned mixture, placing it in a tubular furnace, and carbonizing it in a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0082] Example 4
[0083] (1) 20 g of natural pine wood was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified natural pine wood.
[0084] (2) The delignified natural pine wood of step (1) was placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization was completed, the wood was cooled to room temperature, the product was collected, and the collected product was placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to crush it to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0085] (3) The pre-carbonized wood-based biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0086] (4) Artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected, placed in a tubular furnace, and carbonized under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0087] Example 5
[0088] (1) 20 g of natural basswood was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified natural basswood.
[0089] (2) The delignified natural basswood of step (1) is placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization is completed, the product is cooled to room temperature, and the collected product is placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0090] (3) The pre-carbonized wood-based biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0091] (4) Artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected, placed in a tubular furnace, and carbonized under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0092] Comparative Example 1
[0093] A biomass-derived hard carbon / graphite composite negative electrode material, the main preparation steps of which are as follows:
[0094] (1) 20 g of wood fiber was selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL) and 0.4 M Na2SO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified wood fiber.
[0095] (2) The delignified wood fiber of step (1) is placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization is completed, the wood fiber is cooled to room temperature, the product is collected, and the collected product is placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D 50 =20 μm, and a pre-carbonized wood fiber biomass material was obtained.
[0096] (3) The pre-carbonized wood fiber biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood fiber hard carbon precursor.
[0097] (4) Artificial graphite, the above-mentioned biomass hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected and placed in a tubular furnace for carbonization treatment under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, a treatment time of 8h, and after cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0098] Comparative Example 2
[0099] (1) 20 g of reeds were selected and impregnated with a mixed solution of 2.5 M NaOH (25 mL), 0.4 M Na2SO3 (50 mL), 0.4 M Ca(OH)2 (50 mL) and 0.4 M Na2CO3 (50 mL), and then further treated with 30% H2O2 (30 mL) to obtain delignified and desiliconized reeds.
[0100] (2) The de-lignined and de-siliconized reeds of step (1) were placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5°C / min, a pre-carbonization temperature of 500°C, and a treatment time of 2 hours. After the pre-carbonization was completed, the reeds were cooled to room temperature, the products were collected, and the collected products were placed in a ball mill and ball-milled at a speed of 500 rpm for 2 hours to be crushed to D50 =20 μm, and pre-carbonized reed biomass material was obtained.
[0101] (3) The pre-carbonized reed biomass material of step (2) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a reed hard carbon precursor.
[0102] (4) Artificial graphite, the above-mentioned biomass hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected and placed in a tubular furnace for carbonization treatment under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, a treatment time of 8h, and after cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0103] Comparative Example 3
[0104] (1) 20 g of natural poplar wood was placed in a muffle furnace and pre-carbonized in an air atmosphere at a heating rate of 5 °C / min, a pre-carbonization temperature of 500 °C, and a treatment time of 2 h. After the pre-carbonization was completed, the wood was cooled to room temperature, the product was collected, and the collected product was placed in a ball mill and ball-milled at a speed of 500 rpm for 2 h to be crushed to D 50 =20 μm, and a pre-carbonized wood-based biomass material was obtained.
[0105] (2) The pre-carbonized wood-based biomass material of step (1) is immersed in a 1 mol / L hydrochloric acid solution for 4 hours. After the immersion is completed, it is washed with deionized water and ethanol until it is neutral, and then placed in a vacuum drying oven at 100° C. for 10 hours to obtain a wood-based hard carbon precursor.
[0106] (3) Artificial graphite, the above-mentioned wood-based hard carbon precursor, condensed oil and PVP are added into a fusion device at a mass ratio of 50:50:5.4:5 for fusion treatment to obtain a mixture of biomass hard carbon and graphite; the above-mentioned mixture is collected, placed in a tubular furnace, and carbonized under a N2 atmosphere at a heating rate of 2°C / min, a carbonization temperature of 900°C, and a treatment time of 8h. After cooling to room temperature, a biomass-derived hard carbon / graphite composite negative electrode material is obtained.
[0107] At room temperature, the lithium ion fast charge negative electrode materials prepared by Examples 1 to 5, Comparative Examples 1 to 3 and graphite negative electrode materials were mixed with conductive agent, CMC and SBR in a weight ratio of 95.5:1.5:1.5:1.5, and coated on the current collector copper foil to obtain a working electrode. A metal lithium sheet was used as the counter electrode, the electrolyte used 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (1:1), and the separator was CELGARD, and assembled into a battery.
[0108] Performance test methods and results:
[0109] 1. D 50 Particle size: The particle size D of the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 was measured by a laser particle size analyzer Malvern 3000. 50 .
[0110] 2. True density: The true density of the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 was tested by a gas replacement method.
[0111] 3. Tap density: The tap density of the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 was tested by a tap density tester AUTOTAP.
[0112] 4. Specific surface area: The specific surface area of the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 was tested by a specific surface analyzer NOVA-Touch.
[0113] 5. First charge specific capacity, first discharge specific capacity and first coulombic efficiency: The first charge specific capacity, first discharge specific capacity and first coulombic efficiency of the batteries prepared with the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 were tested at a current density of 0.2C and a charging voltage limit of 0.005-2V.
[0114] 6. 5C / 0.2C rate performance and capacity retention: The rate performance and 100-cycle capacity retention of the batteries prepared with the negative electrode materials of Examples 1-5, graphite and Comparative Examples 1-3 were tested at a 5C / 0.2C rate.
[0115] Table 1 Battery performance test results of each embodiment
[0116]
[0117] From the test results in Table 1, it can be seen that the battery using the biomass-derived hard carbon / graphite composite material prepared by the present invention as the negative electrode material of the lithium-ion battery has a higher specific capacity and better fast charging performance than the ordinary graphite negative electrode material. According to the results of Examples 1 to 3, it can be seen that the 50 / 50 graphite / hard carbon mixing ratio provides a greater first coulombic efficiency and excellent rate performance, because: as the graphite / hard carbon mixing ratio increases, it is beneficial to improve the first coulombic efficiency of the biomass-derived hard carbon / graphite composite negative electrode material, but its first charge specific capacity will decrease accordingly, which can be attributed to the fact that the multi-particle bonding of graphite will create more graphite gaps. As the graphite ratio increases, most of the lithium ions are embedded in the graphite gaps after the discharge process, and most of them can return to the metal negative electrode in the subsequent charging process, so that its first charge specific capacity is approximately close to the first discharge specific capacity, which is manifested as a high first coulombic efficiency, thereby avoiding the situation where the SEI film consumes part of the lithium ions and reduces the charge and discharge efficiency of the electrode material.
[0118] At the same time, the increase in graphite content will lead to an increase in the particle size of the composite electrode material. The greater the van der Waals force that needs to be overcome when lithium ions are embedded, the longer the channel for embedding and detaching is, which is not conducive to quickly reaching a fully embedded lithium state, thereby reducing the charge and discharge performance of the composite electrode material. According to the results of Comparative Examples 1 to 2 and Example 1, compared with the use of wood fiber and reed as hard carbon raw materials (Comparative Examples 1 to 2), the natural poplar, pine or basswood has a higher tap density and a better match with graphite. At the same time, the appropriate ratio of graphite / hard carbon mixing can bring about positive changes in the thickness, density and uniformity of the coating layer, improve the uniformity of the mixed negative electrode current and the lithium precipitation phenomenon during rapid charging. Therefore, the biomass-derived hard carbon / graphite composite material prepared by wood in the present invention has the characteristics of uniform particle size distribution, high specific capacity, good rate performance and good uniformity of current density, and has good application and promotion value.
Claims
1. A biomass-derived hard carbon / graphite composite negative electrode material, characterized in that: The invention comprises hard carbon and graphite; the carbon source of the hard carbon is delignified wood-based biomass; and the mass ratio of the hard carbon to the graphite is 1:(0.33-3).
2. The biomass-derived hard carbon / graphite composite negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The wood-based biomass is wood, preferably one or more of poplar, pine, fir and basswood; (2) The graphite is one or more of artificial graphite, natural flake graphite, mesophase carbon microspheres and expanded graphite; (3) The particle size D of the composite negative electrode material 50 11-18μm; (4) The true density of the composite negative electrode material is 2-3 g / cm 3 , preferably 2.2-2.3g / cm 3 ; (5) The tap density of the composite negative electrode material is 0.9-1.2 g / cm 3 , preferably 0.95-1.05g / cm 3 ; (6) The specific surface area of the composite negative electrode material is 2.5-3.5 m 2 / g; (7) In the composite negative electrode material, the mass ratio of the hard carbon to the graphite is 1:0.8-1.
5.
3. The biomass-derived hard carbon / graphite composite negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The wood-based biomass is poplar, pine or basswood; (2) The graphite is artificial graphite; (3) The particle size D of the composite negative electrode material 50 12μm, 13μm, 14μm, 16μm or 17μm; (4) The true density of the composite negative electrode material is 2.23 g / cm 3 , 2.24g / cm 3 , or 2.25g / cm 3 ; (5) The tap density of the composite negative electrode material is 0.95 g / cm 3 , 0.99g / cm 3 , 1.00g / cm 3 , 1.01g / cm 3 , or 1.02g / cm 3 ; (6) The specific surface area of the composite negative electrode material is 2.7 m 2 / g, 3.1m 2 / g, 3.2m 2 / g, or 3.5m 2 / g; (7) In the composite negative electrode material, the mass ratio of the hard carbon to the graphite is 1:0.33, 1:1 or 1:
3.
4. A method for preparing a biomass-derived hard carbon / graphite composite negative electrode material according to any one of claims 1 to 3, characterized in that: It includes the following steps: S1: pre-carbonizing the delignified wood-based biomass to obtain pre-carbonized wood-based biomass; S2: crushing and acid-leaching the obtained pre-carbonized wood-based biomass to obtain a wood-based biomass hard carbon precursor; S3: fusing and carbonizing the obtained wood-based biomass hard carbon precursor, graphite, dispersant and coating agent to obtain the biomass-derived hard carbon / graphite composite negative electrode material.
5. The method according to claim 4, characterized in that It meets one or more of the following conditions: (1) In step S1, the delignified wood-based biomass is prepared by the following steps: S0: soaking the wood-based biomass in a mixed solution of an aqueous sodium hydroxide solution and an aqueous sodium sulfite solution, and treating with hydrogen peroxide; (2) In step S1, the pre-carbonization reaction is carried out in a muffle furnace; (3) In step S1, the reaction temperature of the pre-carbonization is 350-600°C, preferably 500°C; (4) In step S1, the pre-carbonization temperature rise rate is 4-6°C / min, preferably 5°C / min; (5) In step S1, the pre-carbonization reaction time is 1-3 hours, preferably 2 hours.
6. The method according to claim 5, characterized in that It meets one or more of the following conditions: (1) In step S0, the molar ratio of the sodium hydroxide to the sodium sulfite is (3-4):1, preferably 3.125:1; (2) In step S0, the concentration of the sodium hydroxide aqueous solution is 1-3 mol / L, for example, 2.5 mol / L; (3) In step S0, the concentration of the sodium sulfite aqueous solution is 0.3-0.5 mol / L, for example 0.4 mol / L; (4) In step S0, the mass volume ratio of the wood-based biomass to the mixed solution is (0.1-0.5) g:1 mL, preferably (0.2-0.3) g:1 mL, for example 0.27 g:1 mL; (5) The volume ratio of the mixed solution to hydrogen peroxide is (2-3):1, preferably 2.5:1; (6) The concentration of the hydrogen peroxide is 25%-30%, preferably 30%.
7. The method according to claim 4, characterized in that It meets one or more of the following conditions: (1) In step S2, the pulverizing operation is performed in a ball mill; the rotation speed of the ball mill is 400-800 rpm, preferably 500 rpm; (2) In step S2, the crushing time is 1-5 hours, preferably 2 hours; (3) In step S2, the particle size D of the crushed material 50 5-30 μm, preferably 20 μm; (4) In step S2, the acid used for acid leaching is one or more of hydrochloric acid, sulfuric acid and nitric acid, such as hydrochloric acid; (5) In step S2, the concentration of the acid used in the acid leaching is 0.8-1.5 mol / L, preferably 1 mol / L; (6) In step S2, the acid leaching time is 3-5 hours, preferably 4 hours; (7) In step S2, after the acid leaching is completed, washing and drying are required; preferably, the washing is washing with deionized water and ethanol in sequence; the drying method is preferably vacuum drying; the drying temperature is preferably 80-100°C, more preferably 100°C; the drying time is preferably 8-24h, more preferably 10h.
8. The method according to claim 4, characterized in that It meets one or more of the following conditions: (1) In step S3, based on the sum of the wood-based biomass hard carbon precursor and the graphite, the mass ratio of the sum of the wood-based biomass hard carbon precursor and the graphite to the dispersant is 100:(2.5-8.0), for example, 100:5; (2) In step S3, based on the sum of the wood-based biomass hard carbon precursor and the graphite, the mass ratio of the sum of the wood-based biomass hard carbon precursor and the graphite to the coating agent is 100:(1-25), for example, 100:5.4; (3) The dispersant is dodecylphenol polyoxyethylene ether or polyvinyl pyrrolidone; (4) The coating agent is an organic substance that forms carbon, such as condensed oil; (5) The coking value of the coating agent is 5%-90%, for example 6%; (6) In step S3, the carbonization reaction is carried out in a tube furnace; (7) In step S3, the carbonization reaction is carried out under an inert atmosphere, preferably nitrogen; (8) In step S3, the carbonization temperature is 500-1000° C., preferably 900° C.; (9) In step S3, the carbonization temperature rise rate is 2-3°C / min, preferably 2°C / min; (10) In step S3, the carbonization time is 4-8 hours, preferably 8 hours; (11) In step S3, after the carbonization is completed, the temperature needs to be lowered to room temperature; preferably, the room temperature is 15-40°C.
9. A biomass-derived hard carbon / graphite composite negative electrode material prepared by the method according to any one of claims 4-8.
10. Use of the biomass-derived hard carbon / graphite composite negative electrode material according to any one of claims 1 to 3, or the biomass-derived hard carbon / graphite composite negative electrode material prepared by the method according to any one of claims 4 to 8 as a negative electrode material.
Citation Information
Patent Citations
Hard carbon / graphite composite negative electrode material and lithium ion battery as well as preparation method and application thereof
CN111244407A
Cited By
Graphite negative electrode material and preparation method and application thereof
CN120453322A